Shape Memory Alloys Modeling and Engineering Applications - Lagoudas, Dimitris C.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
This book provides a working knowledge of the modeling and applications of shape memory alloys (SMAs) to practicing engineers and graduate and advanced undergraduate students with an interest in the behavior and utility of active or multifunctional materials and "smart" structures. SMAs represent a unique material class with the ability to recover seemingly permanent deformations and provide large forces upon heating. These interesting characteristics have led to an ever-expanding variety of engineering applications which address design problems requiring high force actuation in a confined environment. Such applications range from morphing aerospace structures to medical stents and other biomedical devices. Specifically, this book, which includes theory, problems and references, aims to provide readers with the following: Comprehensive introduction to the behavior of shape memory alloys which includes a review of SMA history, a microstructural description of the observed effects and a summary of engineering applications. Review of the experimental characterization methods used to quantitykey aspects of the thermomechanical behavior of SMAs. Introduction to continuum thermodynamics as applied to the development of thermomechanical SMA constitutive models, including methods of numerical implementation. Presentation of additional modeling options which address specialized SMA material behavior such as transformation-induced plasticity and constitutive modeling of magnetic SMAs. Edited by a recognized expert leading a group with a long history of SMA research, Shape Memory Alloys: Modeling and Applications is a necessary book for students and practicing engineers interested in a thorough understanding of shape memory alloys.
to Shape Memory Alloys -- Thermomechanical Characterization of Shape Memory Alloy Materials -- Thermomechanical Constitutive Modeling of SMAs -- Numerical Implementation of an SMA Thermomechanical Constitutive Model Using return Mapping Algorithms -- Modeling of Transformation-Induced Plasticity in SMAs -- Extended SMA Modeling -- Modeling of Magnetic SMAs.
Keywords: Materials science; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Continuum mechanics; Mechanical engineering; Materials -- Surfaces; Thin films; Materials Science; Materials Science, general; Engineering Thermodynamics, Heat and Mass Transfer; Continuum Mechanics and Mechanics of Materials; Mechanical Engineering; Surfaces and Interfaces, Thin Films; Electronic books